Nano/micron particles released from newspapers under different reading conditions - Khajornsak Sopajaree (2018)
© 2018 Elsevier B.V. Despite the extensive use of the Internet, printed newspapers remain a primary information source. In this study, reading a newspaper in a relatively confined or poorly ventilated indoor space was simulated to determine the profile of particles released from the newspaper into the air. The consecutive simulated conditions were reading without agitation of the newspaper (NoAg), followed by reading with agitation of the newspaper (Ag) and post-reading absent the newspaper (PostR), repeated with four newspapers. We found that particle number concentration (ΣN) fell during Ag owing to electroadhesion of ultrafine particles (<200 nm) caused by static charges created by friction between the paper surface and the air as a result of newspaper agitation. Conversely, particle surface area concentrations (ΣA) and particle volume concentrations (ΣV) increased significantly during Ag. This was because the larger, fine (1–2.5 μm) and coarse mode (2.5–10 μm), particles were detached from the newspaper during agitation due to inertial detachment – the release of even a small number of these particles contributing greatly to ΣA and ΣV. The critical particle number diameter (CPND) occurred at 207–310 nm. Particles smaller than this were subject to electroadhesion during Ag. The critical particle volume diameter (CPVD) occurred at 130–497 nm. Particles larger than this were subject to inertial detachment during Ag. These observations indicate that the electroadhesion of smaller particles and the inertial detachment of larger particles occur simultaneously. Particle mass concentrations were found to be as high as 168.7–534.3 μg m−3. However, these findings of high potential concentrations were based on the measurement in relative small micro-environment. The inhalation of such concentrations is a health risk for people who regularly read newspapers in a relatively confined or poorly ventilated indoor space.